Strategies for Improving Life Skills in Learning Islamic Religious Education for Students in Makassar - Muhammadong, Muhammadong; Zainuddin, M. Said; Bachtiar, Ishak; Rizal, Andi (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract This study describes the content of life skills in learning Islamic Religious Education. Through a qualitative approach, this research uses a literature review method. The objectives to be obtained are to provide in-depth assumptions about the material under study related to perceptions not on the basis of numerical judgments. The results of the research show that the life skills possessed can be implemented in society based on the religious values that are adhered to. Students can establish communication based on the delivered Islamic Religious Education material. The level of student concern is getting higher, communication links can be built in the community and school environment. Life skills education can overcome juvenile delinquency among students because they are already framed by religious norms. Abstrak Penelitian ini mendeskripsikan tentang muatan life skill dalam pembelajaran Pendidikan Agama Islam. Melalui pendekatan kulitatif, penelitian ini menggunakan metode kajian kepustakaan. Adapun tujuan yang ingin diperoleh hendak memberi asumsi mendalam terhadap materi yang diteliti berkaitan dengan persepsi bukan atas dasar penilaian angka. Hasil penelitian menunjukkan bahwa kecakapan hidup yang dimiiki dapat diimplementasikan di masyarakat berdasarkan nilai-nilai agama yang dianut. Siswa dapat menjalin komunikasi berdasarkan materi Pendidikan Agama Islam yang disampaikan. Tingkat kepedulian siswa semakin tinggi, jalinan komunikasi dapat dibangun dilingkungan masyarakat dan sekolah. Pendidikan life skill dapat mengatasi kenakalan remaja dikalangan siswa karena mereka sudah terbingkai dengan norma keagamaan. Kurikulum yang disampaikan di kelas memuat pengembangan karakter sehingga siswa dapat mengatasi dekadensi moral yang terjadi di masyarakat.